Wrong Tube: Tracheal Obstruction from Megaesophagus - Adam Pearl; Abishek Roka (Clinical Practice and Cases in Emergency Medicine)
Case Presentation: Our patient presented in respiratory distress with stridor with the chief complaint of “inhaled a piece of pizza.” Foreign body airway obstruction algorithmic evaluation was followed but revealed megaesophagus compressing the trachea. Discussion: Megaesophagus is a disorder characterized by diffuse dilation with decreased peristalsis. It is commonly divided into congenital and acquired etiologies. Most documented cases have been secondary to longstanding achalasia and typically present as heartburn and regurgitation. It is imperative to keep broad differentials and avoid anchoring bias in patient evaluation. This rare case of respiratory distress secondary to a gastrointestinal issue highlights the importance of a broad differential and offers insight into a seldom reported occurrence.